2021
DOI: 10.1038/s41598-020-80564-y
|View full text |Cite
|
Sign up to set email alerts
|

False negatives in GBA1 sequencing due to polymerase dependent allelic imbalance

Abstract: A variant in the GBA1 gene is one of the most common genetic risk factors to develop Parkinson’s disease (PD). Here the serendipitous finding is reported of a polymerase dependent allelic imbalance when using next generation sequencing, potentially resulting in false-negative results when the allele frequency falls below the variant calling threshold (by default commonly at 30%). The full GBA1 gene was sequenced using next generation sequencing on saliva derived DNA from PD patients. Four polymerase chain reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In addition, there is evidence to suggest that the choice of polymerase used could be a factor in the accuracy of NGS variant identification. A recent study performed a large-scale screening of GBA1 based on an NGS protocol and found a significant number of false negatives due to a polymerase-dependent allelic imbalance (den Heijer et al, 2021 ). After performing a structured assessment of varied PCR conditions, they found that changing the polymerase used led to the resolution of these false negatives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, there is evidence to suggest that the choice of polymerase used could be a factor in the accuracy of NGS variant identification. A recent study performed a large-scale screening of GBA1 based on an NGS protocol and found a significant number of false negatives due to a polymerase-dependent allelic imbalance (den Heijer et al, 2021 ). After performing a structured assessment of varied PCR conditions, they found that changing the polymerase used led to the resolution of these false negatives.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of GBA1 gene rearrangements cannot be sufficiently captured using most current NGS methods. Several recent studies using NGS technology without Sanger sequencing validation have not reported the presence of recombinant alleles, including a recent study performed on more than 3,000 PD cases (den Heijer et al, 2020). Thus, it is likely that the results presented may be an underestimation (Zampieri et al, 2017).…”
Section: Challenges In Detecting Recombinant Allelesmentioning
confidence: 91%
See 1 more Smart Citation
“…Strategies to specifically analyze the GBA1 as a single gene using NGS technology have been developed [167][168][169]. Such NGS strategies allow the identification of single base pair variants and recombinant alleles (excluding the Recdelta55) with high specificity and sensitivity [167,169].…”
Section: How Should Molecular Testing Be Performed?mentioning
confidence: 99%
“…Strategies to specifically analyze the GBA1 as a single gene using NGS technology have been developed [167][168][169]. Such NGS strategies allow the identification of single base pair variants and recombinant alleles (excluding the Recdelta55) with high specificity and sensitivity [167,169]. Conversely, analysis of the GBA1 gene as part of gene panels using well designed NGS strategies that consider the presence of the pseudogene, allows only the identification of point mutations, while fail to identify both large deletions and recombinant alleles due misalignment of reads with the homologous pseudogene [170][171][172][173][174].…”
Section: How Should Molecular Testing Be Performed?mentioning
confidence: 99%